Cellulose Based Photonic Materials Displaying Direction Modulated Photoluminescence - Santos, Molíria V.; Maturi, Fernando E.; Pecoraro, Édison; Barud, Hernane S.; Lima, Laís R.; Ferreira, Rute A. S.; Carlos, Luís D.; Ribeiro, Sidney J. L. (Frontiers in Bioengineering and Biotechnology, 2021)
Photonic materials featuring simultaneous iridescence and light emission are an attractive alternative for designing novel optical devices. The luminescence study of a new optical material that integrates light emission and iridescence through liquid crystal self-assembly of cellulose nanocrystal-template silica approach is herein presented. These materials containing Rhodamine 6G were obtained as freestanding composite films with a chiral nematic organization. The Scanning Electron Microscopy (SEM) confirms that the cellulose nanocrystal film structure comprises multi-domain Bragg reflectors. The optical properties of these films can be tuned through changes in the silica/cellulose nanocrystals relative content. Moreover, the incorporation of the light-emitting compound allows a complementary control of the optical properties. The photonic structure effects on the emission properties were investigated. Overall, such findings demonstrated that the photonic structure plays the role of direction-dependent inner-filter, causing selective suppression of the light emitted with angle variation detection.